2021
DOI: 10.1111/jfpp.15548
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Pinus halepensis Mill. seed oil: Physicochemical characteristics, bioactive compounds, and antioxidant activity as affected by location and extraction method

Abstract: In this study, physicochemical characteristics, phytochemical compositions, and antioxidant activities of Pinus halepensis Mill. seed oils (PHSO) from two geographical origins (Algeria and Turkey) and obtained through two different extraction processes (cold pressing and solvent extraction) were determined. PHSO were majorly consisted of linoleic and oleic acids. Cold pressing yielded oils with lower peroxide and totox values, higher tocopherols contents (309.42–318.04 mg/100 g), higher DPPH‐radical scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The correlation between polyphenol content and antioxidant activity in plant extracts has been explored in various studies. In this regard, the study of Ait Atmane et al [40] found a substantial correlation (R² = 0.95) between TPC and DPPH in P. halepensis seeds. Additionally, we can observe that there is a good correlation between TPC, reducing sugar and DPPH, which suggests that the antioxidant activities in pinecone extracts may be attributed to the presence of phenolic compounds and reducing sugars.…”
Section: Discussionmentioning
confidence: 91%
“…The correlation between polyphenol content and antioxidant activity in plant extracts has been explored in various studies. In this regard, the study of Ait Atmane et al [40] found a substantial correlation (R² = 0.95) between TPC and DPPH in P. halepensis seeds. Additionally, we can observe that there is a good correlation between TPC, reducing sugar and DPPH, which suggests that the antioxidant activities in pinecone extracts may be attributed to the presence of phenolic compounds and reducing sugars.…”
Section: Discussionmentioning
confidence: 91%